Epigallocatechin-3-Gallate Accelerates Relaxation and Ca2+ Transient Decay and Desensitizes Myofilaments in Healthy and Mybpc3-Targeted Knock-in Cardiomyopathic Mice - Friedrich, Felix W.; Flenner, Frederik; Nasib, Mahtab; Eschenhagen, Thomas; Carrier, Lucie (Frontiers in Physiology, 2016)
Background. Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiac muscle disease with left ventricular hypertrophy, interstitial fibrosis and diastolic dysfunction. Increased myofilament Ca2+ sensitivity could be the underlying cause of diastolic dysfunction. Epigallocatechin-3-gallate (EGCg), a catechin found in green tea has, been reported to decrease myofilament Ca2+ sensitivity in HCM models with troponin mutations. However, whether this is also the case for HCM-associated thick filament mutations is not known. Therefore, we evaluated whether EGCg affects the behavior of cardiomyocytes and myofilaments of a HCM mouse model carrying a gene mutation in cardiac myosin-binding protein C and exhibiting both increased myofilament Ca2+ sensitivity and diastolic dysfunction. Methods and Results. Acute effects of EGCg were tested on fractional sarcomere shortening and Ca2+ transients in intact ventricular myocytes and on force-Ca2+ relationship of skinned ventricular muscle strips isolated from Mybpc3-targeted knock-in (KI) and wild-type (WT) mice. Fractional sarcomere shortening and Ca2+ transients were analyzed at 37 °C under 1-Hz pacing in the absence or presence of EGCg (1.8 µM). At baseline and in the absence of Fura-2, KI cardiomyocytes displayed lower diastolic sarcomere length, higher fractional sarcomere shortening, longer time to peak shortening and time to 50% relengthening than WT cardiomyocytes. In WT and KI neither diastolic sarcomere length nor fractional sarcomere shortening were influenced by EGCg treatment, but relaxation time was reduced, to a greater extent in KI cells. EGCg shortened time to peak Ca2+ and Ca2+ transient decay in Fura-2-loaded WT and KI cardiomyocytes. EGCg did not influence phosphorylation of phospholamban. In skinned cardiac muscle strips, EGCg (30 µM) decreased Ca2+ sensitivity in both groups. Conclusion. EGCg fastened relaxation and Ca2+ transient decay to a larger extent in KI than in WT cardiomyocytes. This effect could be partially explained by myofilament Ca2+ desensitization.